(untitled) (Indonesian Economic Justice Review, 2025)
This paper examines the issue of gender inequality in Indonesia’s labor market and the effectiveness of government policies in promoting women’s economic empowerment. Despite significant advances in education and legal protections for women in Indonesia, gender disparities persist, particularly in the workforce. Women are underrepresented in high-paying sectors and continue to face challenges such as the gender pay gap, limited access to career advancement opportunities, and discrimination in the workplace. The study explores the impact of various government policies, such as affirmative action programs, maternity leave regulations, and women’s entrepreneurship initiatives, in improving women’s economic rights and opportunities. It critically assesses whether these policies have succeeded in dismantling barriers to women’s full participation in the workforce and reducing gender-based economic disparities. The paper also examines the role of cultural norms and the informal economy in perpetuating gender inequality, particularly for rural women and women from ethnic minorities. Through statistical analysis and case studies, the paper identifies both successes and shortcomings in promoting gender equality in Indonesia’s labor market and offers policy recommendations aimed at increasing women’s participation in the formal workforce, enhancing their economic empowerment, and promoting gender justice.